2020
DOI: 10.3390/ijerph17030992
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Based Substance Use Interventions: Opportunities for Gender-Transformative Health Promotion

Abstract: Drawing on data from a scoping review on sex, gender and substance use, this narrative review explores the use of gender-informed and technology-based approaches in substance use prevention and health promotion interventions. With an ever-changing landscape of new technological developments, an understanding of how technology-based interventions can address sex, gender, and intersecting equity considerations related to substance use is warranted. Current technology-based approaches to substance use prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Funding: The work described in this article and several other articles in this special issue [5,[16][17][18][19] was supported by a grant from the Canadian Institutes of Health Research, Institute of Gender and Health. Grant # 384548.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Funding: The work described in this article and several other articles in this special issue [5,[16][17][18][19] was supported by a grant from the Canadian Institutes of Health Research, Institute of Gender and Health. Grant # 384548.…”
Section: Discussionmentioning
confidence: 99%
“…Once we sifted through these, we found that the muddy conceptual use of sex and/or gender prevented us from confidently carrying out our intended overarching systematic review. Instead, based on this material, we developed several scoping reviews [5,16,18,19] and one small systematic review [17] because terms were either misused or imprecise, or in some cases conflated or used in contradictory ways in a single article. Our intention for systematically surveying the current evidence on sex, gender and substance use was undermined because precise engagement with sex and gender in research was, in essence, missing in action.…”
Section: Issues With Language and Conceptual Claritymentioning
confidence: 99%
See 2 more Smart Citations
“…The programme changed normative beliefs, reduced substance use among the girls, and reduced alcohol consumption among their mothers. 30 Interventions to deal with alcohol consumption on college campuses in Canada have included peer run programmes to promote examination of, and change in, the gender norms and inequities that underlie alcohol use to reduce consumption and promote health. In doing so the programmes work to empower women to question the alcohol industry's gendered marketing approaches.…”
Section: Adopting a Gender Transformative Approach To Counter Industry Tacticsmentioning
confidence: 99%